Justice, Trust, Perceived of Risk and Voluntary Tax Compliance in MSME - Nitami Galih Pangesti; Bani Alkausar; Prinintha Nanda Soemarsono; Hanifiyah Yuliatul Hijriah; Azrul Abdullah (TIJAB (The International Journal of Applied Business), 2023)
Background: Tax compliance has become a focused problem in various countries. Especially for developing countries with inadequate law enforcement, tax systems, and taxpayer awareness, this will indirectly impact high rates of taxpayer non-compliance. The issue of low taxpayer compliance is not a significant problem to solve, considering that the domino effect will cause more critical issues in the future. Objective: This study tries to demonstrate additional elements that affect tax compliance, such as the psychological factors of taxpayers and to find out the motives that influence taxpayers. It becomes essential to consider how a person's behavior is influenced by self-perception regarding the system, beliefs, and sanctions before the taxpayer finally voluntarily fulfills their tax obligations. Method: Through the use of a survey, this study employs a quantitative methodology. The poll was conducted via distributing Google forms with questionnaires for respondents to complete on their own. Then, using AMOS Graphic, structural equation modeling (SEM) analytic techniques were used to analyze the data. Results: This study demonstrates that trust and voluntary tax compliance are unaffected by conceptions of fairness (procedural justice, distributive justice, and retributive justice).  Meanwhile, perceptions of risk and trust affect voluntary tax compliance. Conclusion: This shows that MSME taxpayers carry out voluntary tax compliance because they believe that the tax authority can detect non-compliance. In addition, MSME taxpayers increase voluntary tax compliance to avoid penalties due to tax risks arising from the internal and external risks they have. Keywords: voluntary tax compliance; perceptions of justice; trust; perception of risk; MSME